Persepsi Guru Terhadap Hubungan Pengajaran Dengan Masalah Disiplin Pelajar Di Bilik Darjah - Yusuf, Min (2001)

(untitled)
The study intended to examine the perception of teachers pertaining teaching with discipline problem of the students in the classroom. The objectives of this study are to observe 1) the relationship between the teaching planning strategies and discipline problem of the students in the classroom. 2) the relationship between the implementation of the teaching strategies and the discipline problem of the students in the classroom . 3) the relationship between the assessment of the teaching strategies and discipline problem of the students in the classroom. 140 respondents selected from five secondary school in the district of Padang Terap / Pendang. A set of questionaire with four scale was distributed in collecting the data. All the data gathered was analyzed at p = 0.05 using descriptive and Pearson Correlation. The result indicated that there are; 1) a positive and significant relationship ( r = 0.70, p = 0.00 ) between the teaching planning strategies and discipline problem of the students in the classroom. 2) a positive and significant relationship ( r = 0.874 , p = 0.00) between the implementation of the teaching strategies and the discipline problem of the students in the classroom. 3) a positive and significant relationship ( r = 0.70 , p = 0.00) between the assesment of the teaching strategies and discipline problem of the students in the classroom. Based on finding, it is suggested that the teachers in the district of Padang Terap / Pendang should strive to maintain effort to students discipline problem especially students discipline in the classroom.